Chemical, Nutritional Analysis, Quality of Essential Oil of Eruca Sativa and it ̓s Potential Antimicrobial Activity - Kamel, Alaa Rayes; Selim, Yasser A.; Mohammed, Nahed Shehata; Abdel Ghaffar, Nehal Abdel Latif Al Sayed; Mohammad, Batoul N. A. (جامعة الزقازيق - كلية التربية النوعية, 2022)
تهدف هذه الدراسة إلى التحقق من الجودة والقيمة الغذائية والخصائص العلاجية لزيت الجرجير العطري. قيمت دراستنا القيمة الغذائية لزيت الجرجير العطري من خلال تحديد محتوى الرطوبة والكربوهيدرات والفيتامينات والعناصر المعدنية (الغذائية والسامة) والأحماض الدهنية. أيضًا، تم تحديد جودة الزيت من خلال الاختبارات الكيميائية. تم تحديد محتوى الفينول ومحتوى الفلافونويد للزيت. قيمت هذه الدراسة أيضًا نشاط الزيت كمضاد للميكروبات من خلال اختبارين مختلفين. كان محصول الزيت العطري المستخلص (وزن/ وزن) ۰.۳ % وتم تحليله كيميائياً. تظهر نتائج الدراسة أن للزيت قيمة غذائية عالية ثبت أنها غنية بشكل خاص بالعناصر الغذائية والأحماض الدهنية. أشارت النتائج إلى أن الزيت العطري لديه مقاومة أعلى للأكسدة، وجودة أعلى، ومدة صلاحية أطول، وصالح للأكل ومناسب للاستخدام في السلطة وصوصات الشيكولاته أو زيت للطبخ. أظهرت النتائج أن الزيت ذات فعالية كبيرة كمضاد بكتيريا، بما في ذلك سبعة أنواع من البكتيريا المسببة للأمراض البشرية والتي أظهرت مقاومة ضد بعض المضادات الحيوية. This study aims to investigate the quality, nutritional value and therapeutic properties of essential oil of the Eruca sativa Mill. Our study evaluated the nutritional value of essential oil of the E. sativa by locating the content of moisture, carbohydrates, vitamins, mineral (nutritional and toxic) elements and fatty acids. Also, determined the quality of E. sativa essential oil by physicochemical parameters. Total phenolic content (TPC) and total flavonoids content (TFC) were determined. This study also evaluated the in vitro antimicrobial activities by two methods. The yield of the essential oil extracted (w/ w) was 0.3 % and chemically analyzed. The results of the study show that the oil has a high nutritional value that proved to be particularly rich in mineral nutrients and fatty acids. The results indicated that essential oil of E. sativa has higher resistance to autoxidation, higher quality, longer shelf life, suitable for use as salad, chocolate or cooking oil and edible. The results showed that essential oil of the E. sativa has significant antimicrobial activities against the microorganisms, including seven human pathogenic bacteria showed resistance to some antibiotics.
Keywords: التحليل الكيميائي -- الزيوت العطرية -- نبات الجرجير -- مضادات الميكروبات